Usability of a Mobile Application on Anemia Prevention among Adolescents - Rahayu, Sri; Said, Mohamed Saifulaman Mohamed; Sansuwito, Tukimin; Rachmaniah, Dini (Jurnal Keperawatan Soedirman, 2024)
The availability and usability of a smartphone application in Indonesia for preventing anemia, particularly for adolescents, are understudied due to the large number of health applications available for hematologic diseases. This research aims to provide a comprehensive overview of a mobile application development process to prevent anemia among adolescents and test its usability to the end user. The study analyzed the usability of a hybrid application called "AneMia-Prev" at a junior high school in Serang, Banten, Indonesia. The application was developed through conducting a content review, creating a prototype, and undergoing expert development. The usability was assessed by 15 adolescents using a Think Aloud and Smartphone Usability questionnaire. Meanwhile, data analysis was conducted using Jaspers' iterative 3-cycle model. The AneMia_Prev (TA) application was developed using server-client architecture, MySQL database, Apache Tomcat, and Spring Framework. A usability test was conducted on 15 female end users, with a mean age of 16.8 years and 60.0% of them in grade 8. The application received an overall usability average of 112.5 points, indicating good usability. The study demonstrates the high usability of the prototype, indicating its effectiveness, efficiency, and satisfaction, suggesting that future research could use TA methods with larger sample sizes